Correlation of EGFR gene amplification with invasion and metastasis of non-small cell lung cancer - Jia, X.F.; Li, J.; Zhao, H.B.; Liu, J.; Liu, J.J. (Genetics and molecular research, 2015)
The aim of this study was to explore epidermal growth factor receptor (EGFR) gene amplification and its relationship with cancer invasion and metastasis in non-small cell lung cancer (NSCLC). EGFR amplification in 45 patients with NSCLC and 15 subjects with normal lung tissues was detected by fluorescence in situ hybridization. The relationship between EGFR amplification and the clinicopathologic features of NSCLC was analyzed. EGFR gene amplifications were identified in 2 of 15 normal lung tissues (13.33%) and in 29 of 45 NSCLCs (64.44%). Patients <60 years had a 66.67% EGFR amplification rate, while patients ≥60 years had a rate of 62.50%. The EGFR amplification rates in male and female patients were 64.0% (16/25) and 65.0% (13/20), respectively. Pathologically, the EGFR amplification rate of patients with squamous cell carcinoma was 56.52% (13/23), and with adenocarcinoma was 72.72% (16/22). The EGFR amplification rate in NSCLCs with well-moderate differentiation was lower than in those with poor differentiation; 48.0% (12/25) vs 85.0% (17/20), respectively. Patients with lymph node metastasis had nearly double the amplification rate than those without metastasis; 90.0% (18/20) vs 44.0% (11/25), respectively. The rate of EGFR amplification was significantly higher in NSCLC than in normal lung tissue (64.44 vs 13.33%, P < 0.05), and was not correlated with age or gender (P > 0.05), but increased with clinical stage in NSCLCs (P < 0.05). Overall, these studies found that the rate of EGFR gene amplification was increased significantly in NSCLC and was closely related to lymphatic metastasis and TNM stage.